2022
DOI: 10.1055/s-0041-1740554
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Thrombosis following COVID-19: A Systematic Review

Abstract: Background Arterial and venous thromboses associated with the coronavirus disease 2019 (COVID-19) have been well described. These events are caused by a hypercoagulable state due to endotheliopathy and infection-driven coagulopathy. There has been an ever-increasing number of documented cases of aortic thrombosis (AoT) in COVID-19 patients. We conducted a systematic review of current scientific literature to identify and consolidate evidence of AoT in COVID-19 patients. Methods A systematic review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Although thrombus formation within the right atrium, right ventricle can lead to consecutive pulmonary embolism, this issue is under-reported in the scientific literature and clinical guidelines [ 22 , 23 , 24 , 25 ]. There are also few data on aortic thrombosis in COVID-19 and its combination with venous thrombosis [ 24 , 26 , 27 , 28 , 29 , 30 ]. The results of our study demonstrated that in situ pulmonary artery thrombosis is the most common thrombotic complication identified postmortem.…”
Section: Discussionmentioning
confidence: 99%
“…Although thrombus formation within the right atrium, right ventricle can lead to consecutive pulmonary embolism, this issue is under-reported in the scientific literature and clinical guidelines [ 22 , 23 , 24 , 25 ]. There are also few data on aortic thrombosis in COVID-19 and its combination with venous thrombosis [ 24 , 26 , 27 , 28 , 29 , 30 ]. The results of our study demonstrated that in situ pulmonary artery thrombosis is the most common thrombotic complication identified postmortem.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial and venous thromboses associated with COVID-19 have been reported in the literature [2][3][4][5]. An association has been detected with a state of hypercoagulability, and the risk of developing venous and arterial thromboembolic events is as high as 31% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the start of the COVID-19 pandemic, COVID-19 infections have repeatedly been reported to be associated with thrombotic events [1]. These events include appositional thrombi localized in the thoraco-abdominal aorta and iliac arteries, at times even leading to complete occlusion of these vessels [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%